Biofilm/dendritic cell interactions in a murine model of alveolar bone loss: impact of different alveolar bone loss models in mice with long term dendritic cell-specific depletion - Auersvald, Caroline Moreira (2019)
Porphyromonas gingivalis (Pg) virulence is increased within multi-species biofilm models including Streptococcus gordonii (Sg) and Fusobacterium nucleatum (Fn). Hence, this study aims to evaluate the alveolar bone loss, induced by oral gavage infection with or without ligature, caused by mono-infection with wild type (PgWT) and fimbriae deficient strains of Pg (DPG3) compared to biofilm infection with the same Pg strains as part of multi-species biofilm model. Thirty-six C57BL/6J mice were divided in two different subgroups. The Group Oral Gavage infection was divided into Group 1 (G1) Without Ligature (n=18) and Group 2 (G2) Ligature (n=18). The ligature was around the 2nd Maxillary molar. The G1 and G2 were subdivided in CMC Group (Control); Mono-infection Group that it was subdivided in PgWT and DPG3; and Biofilm infection Group (Fn+Sg) that it was subdivided in Biofilm (Control), the biofilm + PgWT and biofilm + DPG3. The samples were scanned with Computerized Microtomography (uCT) and analyzed in Amira software. The data were submitted to statistical analysis (Mann-Whitney p<0.05). Significance difference was found amongst the mono-infection subgroups in the oral gavage model. Comparing the CMC, PgWT, DPG3 groups, the results showed a higher bone loss in PgWT experimental group. We can conclude that PgWT mono-infection has been shown to develop higher alveolar bone loss in a murine animal with or without a ligature model.